2003
DOI: 10.1108/14779960380000233
|View full text |Cite
|
Sign up to set email alerts
|

A Societral perspective on e‐business adoption

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…The research (Ghane & Akhavan, 2014;Léger, 2010;Liu et al, 2016) emphasizes the direct and indirect influences of social capital on perceiving, applying, and evaluating e-business solutions. Studies (e.g., Pouloudi et al, 2003;Oh & Teo, 2006) have also confirmed that social capital and social networks provide valuable opportunities to leverage e-business capabilities to create complex products, diversify operations, and expand market share. Based on this discussion, the following hypothesis is proposed: H1: Social capital has a significant role in achieving e-business proactiveness in responding to the COVID-19 crisis.…”
Section: The Impact Of Social Capital On E-business Proactivenessmentioning
confidence: 96%
See 1 more Smart Citation
“…The research (Ghane & Akhavan, 2014;Léger, 2010;Liu et al, 2016) emphasizes the direct and indirect influences of social capital on perceiving, applying, and evaluating e-business solutions. Studies (e.g., Pouloudi et al, 2003;Oh & Teo, 2006) have also confirmed that social capital and social networks provide valuable opportunities to leverage e-business capabilities to create complex products, diversify operations, and expand market share. Based on this discussion, the following hypothesis is proposed: H1: Social capital has a significant role in achieving e-business proactiveness in responding to the COVID-19 crisis.…”
Section: The Impact Of Social Capital On E-business Proactivenessmentioning
confidence: 96%
“…Today's organizations must be able to sense and exploit ITenabled opportunities in turbulent environments (Oh & Teo, 2006;Pouloudi, Ziouvelou, & Vassilopoulou, 2003). Al Omoush (2020) cites the top management's level of proactiveness as one of the major organizational resources that foster the role of e-business to create a forward-looking strategy for organizational survival.…”
Section: The Impact Of Social Capital On E-business Proactivenessmentioning
confidence: 99%
“…It is a commonplace that for instance languages, customs, religion and laws differ from one location to another, and that these differences may become a barrier to doing business on the Internet (Chong et al, 2003;Zainul et al, 2004; and see, for example, Pouloudi et al, 2003, for a more complete list of cultural features). By the terms local and global we mean local culture versus global culture, irrespective of geographical location.…”
Section: Local/globalmentioning
confidence: 99%
“…E-Bay is an example of a global online company. According to Pouloudi et al (2003), E-Bay "developed a business model that eliminated geographic distances and location asymmetries amongst sellers and buyers and moreover brought everybody together in a common virtual marketplace that took into consideration the differences of its users" (p. 147).…”
Section: Local/globalmentioning
confidence: 99%
“…Research has shown that employee engagement and effective learning can increase when an organization has good agility (Nafei, 2016). Besides, managing information technology increases organizational agility and competitive advantage (Altschuller, Gelb, & Henry, 2010;Lee, Sambamurthy, Lim, & Wei, 2008;Madhok & Marques, 2014;Nissen & Rennenkampff, 2017;Pouloudi, Ziouvelou, & Vassilopoulou, 2003). The strength of the integration between structures within the organization and the connectivity the company develops with its partners and consumers will ease it to analyze ambiguous opportunities in a shorter time, in other words, have organizational agility (Seethamraju & Krishna Sundar, 2013).…”
Section: Introductionmentioning
confidence: 99%